Pesticide safety behavior among vegetable farmers in Bangladesh: Evaluating the role of market aggregation services - Ismat Ara Begum; Mohammad Jahangir Alam; Bhavani Shankar; Gregory Cooper; Karl Rich; Tamanna Mastura; Panam Parikh; Nazmun N. Ratna; Suneetha Kadiyala (Heliyon)
Pesticide use in Bangladesh is disproportionately high in vegetable farming compared to other crops like cereals, pulses, and cash crops. This study delves into the knowledge, attitudes, and practices regarding pesticide use among vegetable farmers, focusing on the impact of a digital aggregation service implemented by Digital Green. Based on interviews with 120 vegetable farmers in the LOOP aggregation scheme and 120 non-LOOP vegetable farmers this study indicates that the farmers using the aggregation service have a moderately higher level of food safety knowledge. LOOP farmers scored higher in pesticide safety knowledge (67.83 %) compared to non-LOOP farmers (55 %). Regarding pesticide safety attitudes, LOOP farmers scored 17.39 %, while non-LOOP farmers 4.17 %, reflecting a generally poor attitude toward pesticide application. Regarding practices, 65.55 % of LOOP farmers adhered to scientifically sound methods, compared to 43.10 % of non-LOOP farmers. Although participation in the LOOP program significantly influenced farmers’ pesticide-related knowledge, attitudes, and practices, this study still identifies the need for targeted interventions and training to improve food safety practices among both groups.